Catalytic Performance of Cement Clinker Supported Nickel Catalyst In Glycerol Dry Reforming - Hua, Chyn Lee; Kah, Weng Siew; Khan, Maksudur R.; Chin, S. Y.; Jolius, Gimbun; Cheng, C. K. (Elsevier Ltd, 2014)
The paper reports the development of cement clinker-supported nickel (with metal loadings of 5 wt%, 10 wt%, 15 wt% and 20 wt%) catalysts for glycerol dry (CO2) reforming reaction. XRF results showed that CaO constituted 62.0% of cement clinker. The physicochemical characterization of the catalysts revealed 32-folds increment of BET surface area (SBET) with the addition of nickel metal into the cement clinker, which was also corroborated by FESEM images. Significantly, XRD results suggested different types of Ni oxides formation with Ni loading, whilst Ca3SiO5 and Ca2Al0.67Mn0.33FeO5 were the main crystallite species for pure cement clinker. Temperature-programmed reduction analysis yielded three domains of H2 reduction peaks, viz. centered at approximately 750 K referred to as type-I peaks, another peaks at 820 K denoted as type-II peaks and the highest reduction peaks, type-III recorded at above 1000 K. 20 wt% Ni was found to be the best loading with the highest XG and H2 yield, whilst the lowest methanation activity. Syngas with lower H2/CO ratios (0.6 to 1.5) were readily produced from glycerol dry reforming at CO2-to-Glycerol feed ratio (COR) of unity. Nonetheless, carbon deposit comprised of whisker type (Cv) and graphitic-like type (Cc) species were found to be in majority on 20 wt%Ni/CC catalysts.